Role of the Banking Union in the European Integration Process - Graczyk, Agata (Journal of Finance and Financial Law, 2021)
The main objective of this article is to assess the impact of the banking union on shaping the integration process on the European continent. This has been done by positioning the banking union as a stage leading to a full union of European countries. The basic research question of this study has been formulated as follows: is the banking union project an important element contributing to the full integration of EU banking systems, the implementation of which is necessary to protect the European Union from the effects of future banking crises? This issue was resolved on the basis of an analysis of the available literature and statistical data. The main conclusion of the research undertaken is that: the banking union is a necessary step towards further European integration and is a key element in the integration of European banking systems. However, even the full implementation of the banking union project will not completely eliminate the possibility of banking crises, but may reduce this risk to some extent and thus reduce the costs of potential crises.